The Regulatory State in an Age of Governance - King, R. author. aut Link
XVI, 228 p.
Keywords: Presents an account of the regulatory state and governance. This book examines both key concepts and theories, and important policy domains, and utilizes comparative, historical and transnational perspectives. It questions whether the regulatory state that has developed over the decades is an authoritarian or a liberalizing mode of governance.